How Agile Organizations Use Metrics: A Systematic Literature Mapping - Leal, Stéphanie; Hauck, Jean; Bertan, Monique; Vieira, Gustavo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
Agile Software Development Methods (ASDMs) have addressed the complexity of managing software development processes through small increments, continuous and frequent delivery, openness to change, and work visibility. These practices have been complemented by the use metrics adapted to ASDMs context, generating a large number and types of metrics. Thus, this secondary study presents a Systematic Literature Mapping to understand how agile organizations use metrics. Seven research questions were defined, and 33 primary studies related to the use of agile metrics were selected. The results indicate that most organizations that use agile metrics use Scrum, develop large size general-purpose software products, desktop, or web applications, in small teams. The metrics are selected by primary studies based on literature search, interviews with the team members or expert groups. The majority of the organizations use Product Quality, Resource and Cost, and Process performance metrics, focusing in the agile team, management and customer. The primary studies results indicate that using agile metrics can positively impact the quality of processes, products, and services.